Hematological shift in goat kids naturally devoid of prion protein - Reiten, Malin R. (Front Cell Dev Biol, 2015)
The physiological role of the cellular prion protein (PrP(C)) is incompletely understood. The expression of PrP(C) in hematopoietic stem cells and immune cells suggests a role in the development of these cells, and in PrP(C) knockout animals altered immune cell proliferation and phagocytic function have been observed. Recently, a spontaneous nonsense mutation at codon 32 in the PRNP gene in goats of the Norwegian Dairy breed was discovered, rendering homozygous animals devoid of PrP(C). Here we report hematological and immunological analyses of homozygous goat kids lacking PrP(C) (PRNP(Ter/Ter)) compared to heterozygous (PRNP(+/Ter)) and normal (PRNP(+/+)) kids. Levels of cell surface PrP(C) and PRNP mRNA in peripheral blood mononuclear cells (PBMCs) correlated well and were very low in PRNP(Ter/Ter), intermediate in PRNP(+/Ter) and high in PRNP(+/+) kids. The PRNP(Ter/Ter) animals had a shift in blood cell composition with an elevated number of red blood cells (RBCs) and a tendency toward a smaller mean RBC volume (P = 0.08) and an increased number of neutrophils (P = 0.068), all values within the reference ranges. Morphological investigations of blood smears and bone marrow imprints did not reveal irregularities. Studies of relative composition of PBMCs, phagocytic ability of monocytes and T-cell proliferation revealed no significant differences between the genotypes. Our data suggest that PrP(C) has a role in bone marrow physiology and warrant further studies of PrP(C) in erythroid and immune cell progenitors as well as differentiated effector cells also under stressful conditions. Altogether, this genetically unmanipulated PrP(C)-free animal model represents a unique opportunity to unveil the enigmatic physiology and function of PrP(C).